Business Intelligence - Surma, Jerzy (Business Expert Press, 2011)
Ebook from IG Library ; Concentrates primarily on practical business issues and demonstrates how to apply data warehousing and data analytics to support business decision making. This book progresses through a logical sequence, starting with data model infrastructure, then data preparation, knowledge discovery, and finally the actual use of discovered knowledge.